2015
DOI: 10.3897/neobiota.25.8354
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the local scale colonisation and change in density of a widespread invasive plant species, Lantana camara, in South India

Abstract: Identifying factors that underlie invasive species colonisation and change in density could provide valuable insights into the mechanisms of biological invasions and for invasive species management. We examined a suite of factors potentially influencing the landscape-level invasion of Lantana camara L., one of the most ubiquitous invasive species in South Asia. These factors included disturbance factors like forest fires, historical habitat modification, and edge effects, in addition to factors like propagule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, the species density in the S.AS was higher at the 0–5 cm soil depth than those under other vegetation types, while at 5–10 cm soil depth was the lowest, which suggested that S.AS tended to concentrate seeds on the 0–5 cm soil depth compared with those of other communities. The high density of seeds of S. alterniflora under its own community tended to help to consolidate its colonization and promote its further invasion (Sundaram et al, 2015). Results also showed that the seed species richness and density in the soil seed banks was higher than that of aboveground vegetation, indicating that there would be more potentiality of regeneration from the soil seed banks if the aboveground vegetation were destroyed or seriously damaged.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the species density in the S.AS was higher at the 0–5 cm soil depth than those under other vegetation types, while at 5–10 cm soil depth was the lowest, which suggested that S.AS tended to concentrate seeds on the 0–5 cm soil depth compared with those of other communities. The high density of seeds of S. alterniflora under its own community tended to help to consolidate its colonization and promote its further invasion (Sundaram et al, 2015). Results also showed that the seed species richness and density in the soil seed banks was higher than that of aboveground vegetation, indicating that there would be more potentiality of regeneration from the soil seed banks if the aboveground vegetation were destroyed or seriously damaged.…”
Section: Discussionmentioning
confidence: 99%
“…But the fundamental question of why some introduced species become more abundant and widespread than others still remains only partially answered (Keane & Crawley, 2002; Kolar & Lodge, 2001; van Kleunen et al, 2010). There are various factors that influence the degree of invasion in an ecosystem; these include—among others—fires, historical habitat modification, propagule pressure, release from herbivores, human usage, pollinators, and habitat suitability (Geerts & Adedoja, 2021; Geerts et al, 2016; Geerts, Botha, et al, 2013; Honig et al, 1992; Mangachena & Geerts, 2019; Sundaram et al, 2015). Many hypotheses have been put forward to explain these phenomena (reviewed in Catford et al, 2009).…”
Section: Introductionmentioning
confidence: 99%